The Evaluation of ESP (English Specific Purposes) for Mathematic Education Department Students Based on Need Analysis Approaches - Muhammad, Aris Setiawan; Saparianingsih, Ria (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
English for specific purposes (ESP) is an approach to learning English. ESP be main approach in English language teaching for the English learner who has particular purpose based on needed. Need analysis is part of ESP course because this is first step that must be taken by ESP teacher before beginning ESP course. Evaluation is important that must be taken at the end of learning ESP because it can measure whether the goals of an ESP course have been meet and ensures the program continuous improvement. The purpose of this study is to find out the need of students in learning English in their major and to know about the evaluation of the teacher in learning English for specific purposes in the ESP course or program for Mathematics Education Department at Universitas Muhammadiyah Sukabumi. The researchers using theory from Hutchinson and Water to analyze of student need and course evaluation by the teacher. This research uses descriptive qualitative to collecting, analyzing and describing the data. Data is taken from observation, interview, questionnaire and documentation. The population of this research are 14 people, that are 1 lecturer and 13 students. The data found from observation and interview using a table and from students need at questionnaire answer using a pie chart for data overview. The result from this study found that the average students in Mathematics Education Department has basic English level, they need to mastery English speaking skill (92,3%) to support academic and for career. English is used to understand meaning of sentences (53,8%) for their study literature in their major. The evaluation carried out in the course is done by monitoring evaluation.ESP, The Evaluation, Need Analysis